Enhancing Digital Literacy Through English Language Teaching: A Needs Analysis for English Students at Muhammadiyah University of Mataram - Irwandi, Irwandi; Hidayati, Hidayati; Lukman, Lukman (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The importance of digital literacy has grown significantly, making its integration into English language teaching (ELT) crucial. This study investigated the role of ELT in promoting digital literacy among English students at Muhammadiyah University of Mataram and identified their digital literacy needs. Using a mixed-methods research design, data were collected from students’ need through questionnaires and interviews, which assessed their digital literacy skills, technology use in ELT, and perceived needs for digital literacy development. The findings showed that students were interested in incorporating digital literacy into ELT and identified various digital tools, platforms, and skills they considered essential. Participants emphasized the importance of teacher guidance, language-specific digital resources, and training. The study recommends integrating digital literacy development into the ELT curriculum, providing accessible resources, and exploring further research opportunities. The results offer practical insights for language educators, policymakers, and researchers aiming to enhance digital literacy skills among English Department students through ELT.